The Effect of Supportive Combination Therapeutic Group Therapy on Self Efficacy and Bullying Behavior in Adolescents - Ekawaty, Fadliyana; Martawinarti, RTS Netisa; Rudini, Dini; Sari, Lisa Anita; Sari, Yulia Indah Permata; Nasution, Riska Amalya (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
Background: Adolescence is a transition period from childhood to adulthood which is faced with various challenges and developmental problems. Problems in development can form low self-efficacy and can lead to deviant behavior, one of which is bullying behavior among adolescents. Supportive combo group therapy is one of the therapies that can be done to increase self-efficacy and can help prevent bullying in adolescents. Objective: To determine the effect of supportive combination group therapy on self-efficacy and prevention of bullying behavior in adolescents. Methods: This research design is a quasi-experiment pre-post test with a control group design). The population in this study were all students at SMPIT Uswatun Hasanah Jambi with the exclusion criteria being adolescents who were sick and absent during the activity. The sample was 60 students consisting of 30 students for the control group and 30 students for the intervention group. The intervention was given in 4 sessions,each session with a duration of 45-60 minutes. Data were collected through questionnaires and analyzed using the man whitney test. Results: In the intervention group and control group, there was a significant difference between self-efficacy and bullying behavior in adolescents before and after the intervention with a p value of 0.001 (p < 0.005). Conclusion: Supportive combined therapeutic group therapy increases self-efficacy and can prevent bullying behavior in adolescents.